Giving Effective Presentations - Englehart, Nadine (Operating Room Nurses Association of Canada Journal, 2004)
Apprehension about oral communication, or public speaking is rated as the number one fear among most individuals.1 Developing skill in, and comfort with, public speaking is important whether we are presenting oral reports and proposals, responding to questions, or training co-workers. Effective speakers are able to communicate information in a way that stimulates interest, helps the audience to understand and remember, and influences attitudes and behaviours. Many of us think that effective speakers are born rather than made. In truth most successful speakers work hard and invest a great deal of time and effort in to improving their speaking capabilities. Effective public speaking is a learned skill and activity that requires lots of practice. Like other learned skills, having a strategy with clear action steps can help you achieve your goal.